Praktik Diferensiasi Pembelajaran Strategi Pendidikan Inklusi Di Sekolah Dasar - Zahra, Dzira Rasifa; Muttaqin, Muhammad Fauzan (CV. SINAR HOWUHOWU, 2025)
Inclusive education in elementary schools requires learning strategies that accommodate students’ diverse abilities and learning needs. Differentiated instruction is considered a relevant approach to support inclusive learning. This study aims to describe the practice of differentiated learning as a strategy for inclusive education in elementary schools. The research employed a qualitative descriptive method using classroom observations, teacher interviews, and documentation analysis. The findings indicate that differentiated instruction is implemented through variations in content, learning processes, and learning products adjusted to students’ readiness and learning profiles. This approach enhances student participation, learning motivation, and supports the inclusion of students with special needs. The study concludes that differentiated instruction is an effective strategy for fostering inclusive learning environments in elementary schools